Pencatatan Akuntansi pada Usaha Pengrajin Bambu di Desa Taman Sari Kabupaten Lombok Barat - Muhammad Syukri; Syarifah Massuki Fitri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the application of accounting records that occur in bamboo craftsmen's businesses in Taman Sari Village as well as the challenges and obstacles faced during the business. This research took 5 samples of bamboo craftsmen MSMEs using a sampling method by conducting interviews in order to obtain valid information. Research shows that some bamboo craftsmen do not keep records neatly. Some entrepreneurs record financial income and expenses without considering operational costs, which results in inaccurate recognition of profits/losses from the business. The challenges and obstacles faced by Micro, Small and Medium Enterprises of bamboo craftsmen are that the average level of education and knowledge is still lacking in financial recording. Apart from that, financial management is still not managed professionally in accounting records due to the lack of government role in this field.